Associations between trajectories of perceived racial discrimination and psychological symptoms among African American adolescents - Smith-Bynum, Mia A. (2014)
Many African American adolescents experience racial discrimination, with adverse consequences; however, stability and change in these experiences over time have not been examined. We examined longitudinal patterns of perceived racial discrimination assessed in grades 7 – 10 and how these discrimination trajectories related to patterns of change in depressive and anxious symptoms and aggressive behaviors assessed over the same 4-year period. Growth mixture modeling performed on a community epidemiologically-defined sample of urban African American adolescents (n = 504) revealed three trajectories of discrimination: (1) increasing, (2) decreasing, and (3) stable low. As predicted, African American boys were more frequent targets for racial discrimination as they aged, and were more likely to be in the increasing group. Results of parallel process growth mixture modeling revealed that youth in the increasing racial discrimination group were four times more likely to be in an increasing depression trajectory than youth in the low stable discrimination trajectory. Though youth in the increasing racial discrimination group were nearly twice as likely to be in the high aggression trajectory, results were not statistically significant. These results indicate an association between variation in the growth of perceived racial discrimination and youth behavior and psychological well-being over the adolescent years.